Influência da cultura corporativa nos estilos de uso do orçamento e no desempenho organizacional - Christmann, Letícia (2022)
This research aims to analyze the influence of corporate culture on budget use styles and organizational performance in companies operating in Brazil. The literature in the area has focused on seeking the relationship between corporate culture and the adoption/implementation of management control tools. However, culture provides circumstances that support the use of management control systems, which consequently influence performance. The research took place through a survey, with a quantitative and descriptive approach. The research population is Brazilian companies with operations in Brazil, which use the budget. The sample was defined with the help of the LinkedIn® tool, looking for individuals who occupy controllership positions and related positions in companies with operations in Brazil, obtaining 224 responses. The results show that the results-oriented cultural dimension positively influences the diagnostic use of the budget and is indirectly positively associated with organizational performance. In view of this, it is inferred that the companies analyzed with values, beliefs and norms predominantly oriented towards results and that use the budget as a management control with a diagnostic function, have superior organizational performance. And, companies that emphasize results-oriented or innovation-oriented cultural values, but use budgeting in an interactive format, have lower organizational performance. The evidence found reinforces the importance of aligning cultural values and styles of budget use, aiming at organizational performance. Different cultural dimensions are related to superior organizational performance, however, budget use styles must be analyzed. The results-oriented cultural dimension can be related to the diagnostic and/or interactive use style, and the innovation-oriented cultural dimension is related only to the interactive use of the budget.